Designing a Nutrient Medium for the Accumulation of Microbial Mass of Listeria - N. M. Khaptanova; S. V. Lukyanova; V. I. Kuznetsov; N. G. Gefan; N. M. Аndreevskaya; Zh. A. Konovalova; А. S. Ostyak; V. S. Kosilko (Acta Biomedica Scientifica)
Background. To obtain reliable results of laboratory studies on the identification of Listeria, the presence of certified diagnostic agglutinating Listeria sera is required. An important step in the manufacturing process of such medical devices for in vitro diagnostics requires effective nutrient media for the accumulation of listeriosis microbe. Aim of the research. To develop an effective nutrient medium for the accumulation of bacterial mass of Listeria. Materials and methods. The object of the study was an experimental culture medium for Listeria cultivation. As a control, we used nutrient agar for the cultivation of microorganisms (fish meal hydrolysate, FMH-agar) and meat-peptone agar with 1 % glucose (MPA with 1 % glucose). The specific activity of nutrient media during cultivation of the test strain Listeria monocytogenes 766 was evaluated using a complex of microbiological methods. Results. The optimal base of the nutrient medium for Listeria cultivation has been selected: pancreatic hydrolysate of river magpie fish (Rutilus rutilus lacustris) and hydrolysate of meat water production waste. The qualitative and quantitative composition of the nutrient medium has been developed, its physical, chemical and biological properties have been studied. It was found that after 24 hours of incubation at 37 °C, the nutrient medium provided the growth of typical Listeria colonies. The germination rate was 85 %, which is higher compared to the growth of the culture on MPA with 1 % glucose and GRM agar by an average of 21 % (p < 0,05). Conclusion. The experimental culture medium for Listeria cultivation provided growth of colonies of the test strain L. monocytogenes 766 with the preservation of characteristic cultural, morphological and biochemical properties, and, in terms of germination and growth rate, exceeded the control media. The developed nutrient medium provides effective growth of Listeria and can be used as a medium for the accumulation of microbial mass.